Detection of Factors that Influence Tax Avoidance Using Fraud Diamond Theory - Luluk Indrawayu; Annisa Fitriana; Sutrisno (Jurnal Akuntansi Bisnis dan Humaniora, 2023)
This research aims to determine the factors that influence tax avoidance using fraud diamond theory. This research uses a pressure variable which is proxied by return on assets, an opportunity variable which is proxied by the ratio of independent commissioners, rationalization which is proxied by changing external auditors, an ability variable which is proxied by changing directors and tax avoidance which is proxied by cash effective tax rate. The object of this research is the LQ-45 manufacturing subsector company listed on the Indonesia Stock Exchange for the 2020-2022 period. The research sample selection method used was purposive sampling. The research sample was 36 samples. This research uses multiple linear regression analysis methods. The research results show that the variables of pressure and rationalization have a significant and influential effect on tax avoidance. Meanwhile, the opportunity and ability variables do not have a significant effect on tax avoidance.